A Comparative Study of Reporting Verbs Used in the Introduction Chapters of Bachelor’s Theses and Master’s Theses by Chinese English-Majored Students - Wen, Shuangqing; Pramoolsook, Issra (Indonesian Journal of Applied Linguistics, 2021)
Reporting verbs (RVs), as rhetorical lexical devices, play a key role in academic writing because they enable writers to attribute content to other sources and allow them to convey both the kind of activities reported and their evaluation of the reported information. However, no study has been conducted on how RVs are used differently between bachelor’s theses (BTs) and master’s theses (MTs) in the Chinese context. Through corpus-based and comparative analysis, this study, therefore, aims to analyze and compare the use of RVs between 30 BT Introduction Chapters and 30 MT Introduction Chapters by Chinese English-majored students in terms of denotative potentials and evaluative functions based on Hyland’s (2002) classification framework. The results reveal that RVs used by undergraduate students are smaller in amount and narrower in range compared with those used by master’s students. Concerning the denotative potentials of RVs, a similar distribution of RVs was found in the two corpora. Both undergraduate and master’s students prefer Discourse Act RVs and Research Act RVs to Cognition Act RVs. Regarding their evaluative functions, undergraduate students show a tendency toward non-factive RVs, while master’s students tend to use factive RVs. These findings provide a valuable view of how Chinese English-majored students use RVs in their thesis writing, but their knowledge of the rhetorical functions of this device is still insufficient. The findings might increase thesis writers’ knowledge on the significance of RVs and raise their awareness of using RVs appropriately and effectively in their thesis writing, or even in all kinds of academic discourse. This paper then provides some suggestions for thesis writing courses.